2001
DOI: 10.1046/j.1365-2036.2001.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of intragastric acidity with over‐the‐counter doses of ranitidine or famotidine

Abstract: Background: Histamine H2‐receptor antagonists are available over the counter for the treatment of heartburn. Aim: To compare the effects of low doses of ranitidine and famotidine on intragastric acidity in a three‐way crossover study. Methods: Healthy subjects (12 male, 12 female) were dosed on three occasions with single oral doses of placebo, ranitidine, 75 mg, and famotidine, 10 mg, 1 h after lunch. The pH of gastric aspirates was then measured for 20 h. Subjects ate standard meals and snacks. Analysis of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In line with this, it is important to determine which particular H 2 R antagonist has the earliest onset of H 2 R inhibition in humans. Several studies using human subjects have shown that ranitidine is more prompt than famotidine in controlling gastric acidity [13, 14, 17]. In the present study, we found direct evidence that ranitidine interacts with the human H 2 R much more rapidly than does famotidine.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In line with this, it is important to determine which particular H 2 R antagonist has the earliest onset of H 2 R inhibition in humans. Several studies using human subjects have shown that ranitidine is more prompt than famotidine in controlling gastric acidity [13, 14, 17]. In the present study, we found direct evidence that ranitidine interacts with the human H 2 R much more rapidly than does famotidine.…”
Section: Discussionsupporting
confidence: 66%
“…Several reports have focused on gastric acidity effects in human subjects of the most widely used marked H 2 R antagonists: ranitidine and famotidine [13, 14, 15, 16, 17, 18]. Accumulating clinical data suggest that ranitidine has an earlier onset of action than famotidine, whether administered orally or intravenously [13, 14, 17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the commonly used medical agents has been H 2 receptor antagonists; however, PPI s have recently become superior to H 2 receptor antagonists in treating esophageal mucosal injury and erosive esophagitis due to GERD (31)(32)(33)(34). Despite an adequate treatment regimen, the patient population who are poor or non-responders to PPI treatment will constitute 10-30% of all GERD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The H 2 ‐receptor antagonist, ranitidine, inhibits gastric acid and fluid secretion in both basal and stimulated states, thereby increasing the pH and decreasing the volume of gastric contents available for reflux into the oesophagus 5 . The usual prescription doses of ranitidine are effective in relieving heartburn 6 and pharmacodynamic data indicate that lower doses of ranitidine may also be effective for the treatment of episodic heartburn 7 –9 …”
Section: Introductionmentioning
confidence: 99%